Characterization of silver nanoparticles (AgNPs) synthesized from Piper ornatum leaf extract and its activity against food borne pathogen Staphylococcus aureus - FIRLI RAHMAH PRIMULA DEWI; VUANGHAO LIM; A’LIYATUR ROSYIDAH; FATIMAH FATIMAH; SRI PUJI ASTUTI WAHYUNINGSIH; UMMI ZUBAIDAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Dewi FRP, Lim V, Rosyidah A, Fatimah, Wahyuningsih SPA, Zubaidah U. 2023. Characterization of silver nanoparticles (AgNPs) synthesized from Piper ornatumleaf extract and its activity against food borne pathogen Staphylococcus aureus. Biodiversitas 24: 1742-1748. Staphylococcus aureusis the most recurrent food borne pathogen that commonly resists antibiotics. Silver nanoparticles (AgNPs) have potential to solve bacterial multidrug resistance. This study aims to assess bactericidal activityof AgNPs against S. aureussynthesized from Piper ornatumleaf extract. Biosynthesis was performed by mixing P. ornatumextract with AgNO3aqueous solution and then incubating for 24 h at room temperature under dark condition. The formation of AgNPs was confirmed by changing optical color from light yellowish to dark brown with a peak of UV spectrum at ~500 nm. According to SEM imaging, AgNPs had spherical form whereas EDS analysis revealed strong signal at 3 kV indicating existence of silver element. Meanwhile, face-centered cubic structures of AgNPs were indicated by XRD analysis. FTIR analysis confirmed ketone, flouro, and amine as functional groups presented in extract were essential for the bioreduction of silver nitrate to silver nanoparticles. This study revealed that AgNPs have a potent bactericidal effect. In vitroevaluation using agar well-diffusion assay showed high inhibition zone of S. aureus (14.28±0.26) upon treating with 25 µg/m L AgNPs while MIC value was 5 µg/mL. However, antibiotic erythromycin and chloramphenicol respectively exhibited better inhibition zone and MIC value.